STUDI DESKRIPTIF PENYEBAB KETUBAN PECAH DINI DI RUMAH SAKIT PANEMBAHAN SENOPATI BANTUL - Mariana; Fitria Ayuningtyas, Ika (Universitas Jenderal Achmad Yani Yogyakarta, 2015)
Background: The premature rupture of membrane (PROM) is a controversial issue in midwifery that prevention efforts cannot be done because the exact etiology has not been acknowledged. The PROM may lead to infection to mother and baby, hence may increase the morbidity and mortality of mothers and babies. Objectives: To investigate the etiology of premature rupture of membrane ( PROM) viewed from gemelly, polihidramnion, distency of uterus, and fetal stress factors. Methods: The study was a descriptive research and used documentation study method. The samples used was 111 records in 2013 at Panembahan Senopati Bantul Hospital. Results : The etiology of the PROM in Panembahan Senopati Bantul Hospital were fetal stress (45%), distency of uterus (41,4%), polihidramnion (10,8%) and the least was gemelly (2,7%). Conclusion : The most frequent etiology of the PROM at Panembahan Senopati Bantul Hospital in 2013 was fetal stress (45%). Keywords: Premature Rupture of Membrane, Pregnancy